Subtrochanteric valgus osteotomy in nonunited femoral neck fractures in children: two different fixation methods - Mahmoud Badawy; Sami Ibrahim Sadek; Ahmed Mohamed Abdelwahab; Ibrahim Abdellatif Algohiny (Journal of Orthopaedic Surgery and Research)
Abstract Introduction Nonunion of pediatric femoral neck fractures is a difficult situation for orthopedic surgeons. It can result in devastating results if left untreated. The purpose of the present study was to assess and compare the results of the treatment of nonunited pediatric femoral neck fractures by closed reduction and subtrochanteric valgus osteotomy with two different fixation methods. Patients and methods Seventeen patients with nonunion femoral neck fractures were treated with closed reduction, subtrochanteric osteotomy and fixation with either the proximal humerus internal locking system (PHILOS plate) (group A) (10 patients) or the Wagner technique (group B) (7 patients). The mean age of the patients was 7 years, and the mean follow-up period was 16 months. Results At the end of the follow-up, all patients, the fractures were united. We did not observe any cases of implant failure. There was a statistically significant improvement in the neck shaft angle in both groups from 88.70 ± 3.36 to 129.35 ± 7.34 in group A and from 87 ± 1.91 to 126.78 ± 4.06 in group B. Regarding the clinical outcome and according to the Ratliff concept, half of the cases were good in group A and 57.1% were good in group B. There was no statistically significant difference between the groups regarding time to union, degree of coxa vara correction or the Ratliff concept. Conclusion Both the PHILOS plate and the Wagner technique offer good stable fixation options for nonunited pediatric femoral neck fractures.